Beyond Photochromism: Alternative Stimuli to Trigger Diarylethenes Switching - Qi Ai; Kangjun Lan; Lin Li; Zugang Liu; Xiaoguang Hu (Advanced Science)
Abstract Diarylethenes (DAEs) are typical photochemically reversible type (P‐type) photochromic materials with excellent thermal stability and high fatigue resistance and are widely exploited as photo‐switches for various applications in molecular devices, data storage, photoresponsive materials, and bioimaging, etc. In recent years, there is an increasing number of reports using heat, acid, electrochemistry, etc. to drive the isomerization reaction of DAEs. The response to two or more different stimuli enables multi‐functionality within a single DAE molecule, which would facilitate complex logic‐gate operations, multimode data storage, and increased information density. Herein, the recent advances in DAE systems utilizing stimuli “beyond photo” to trigger the isomerization processes from three perspectives: acidochromism, thermochromism, and electrochromism are reviewed. Emphasis is placed on the molecule design strategies and the underlying mechanisms for cyclization and cycloreversion processes addressed by the alternative stimulus. Then the noticeable applications made in multi‐stimuli responsive DAE systems are summarized. Additionally, the challenges and opportunities of DAE switches driven by stimuli “beyond photo” in the future are also discussed.